Crosstalk between Pseudomonas aeruginosa antibiotic resistance and virulence mediated by phenylethylamine - Ada Muñoz‐Cazalla; José L. Martínez; Pablo Laborda (Microbial Biotechnology, 2023)
Abstract Multidrug efflux pumps are among the main Pseudomonas aeruginosa antibiotic‐resistance determinants. Besides, efflux pumps are also involved in other relevant activities of bacterial physiology, including the quorum sensing‐mediated regulation of bacterial virulence. Nevertheless, despite the relevance of efflux pumps in bacterial physiology, their interconnection with bacterial metabolism remains obscure. The effect of several metabolites on the expression of P. aeruginosa efflux pumps, and on the virulence and antibiotic resistance of this bacterium, was studied. Phenylethylamine was found to be both inducer and substrate of MexCD‐OprJ, an efflux pump involved in P. aeruginosa antibiotic resistance and in extrusion of precursors of quorum‐sensing signals. Phenylethylamine did not increase antibiotic resistance; however, the production of the toxin pyocyanin, the tissue‐damaging protease LasB and swarming motility were reduced in the presence of this metabolite. This decrease in virulence potential was mediated by a reduction of lasI and pqsABCDE expression, which encode the proteins that synthesise the signalling molecules of two quorum‐sensing regulatory pathways. This work sheds light on the interconnection between virulence and antibiotic‐resistance determinants, mediated by bacterial metabolism, and points to phenylethylamine as an anti‐virulence metabolite to be considered in the study of therapies against P. aeruginosa infections.